2007
DOI: 10.1007/s10853-006-1181-6
|View full text |Cite
|
Sign up to set email alerts
|

Crack growth in structural adhesive joints in aqueous environments

Abstract: The adhesive fracture energy, G c , of metallic joints, bonded with a rubber-toughened epoxy adhesive, has been measured using monotonically-loaded tests. Such tests have been conducted in various relative humidities and in water, at 21 o C. Two surface pretreatments have been employed for the substrates prior to bonding: a simple grit-blast and degrease ('GBD') pretreatment or a grit-blast, degrease and silane primer ('GBS') pretreatment. The joints were formed using metallic substrates which were either (a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 28 publications
4
17
0
Order By: Relevance
“…This is similar to data reported for fracture tests in humidity-controlled environments using steel or aluminum adherends at a range of loading speeds [26]. Interfacial failure was only observed at low crack growth rates when moisture could diffuse ahead of the crack tip [26]. Therefore, the present experiments show that, despite the dissimilar strain energy release rates and damage zone sizes in creep and fatigue testing, condensed moisture caused interfacial failure in creep crack growth just as it did in mixed-mode near-threshold fatigue because of the low crack speeds.…”
Section: Effect Of Environment On the P2-etched Aa6061-t6 Systemsupporting
confidence: 88%
See 1 more Smart Citation
“…This is similar to data reported for fracture tests in humidity-controlled environments using steel or aluminum adherends at a range of loading speeds [26]. Interfacial failure was only observed at low crack growth rates when moisture could diffuse ahead of the crack tip [26]. Therefore, the present experiments show that, despite the dissimilar strain energy release rates and damage zone sizes in creep and fatigue testing, condensed moisture caused interfacial failure in creep crack growth just as it did in mixed-mode near-threshold fatigue because of the low crack speeds.…”
Section: Effect Of Environment On the P2-etched Aa6061-t6 Systemsupporting
confidence: 88%
“…This was attributed to moisture diffusion ahead of the crack tip being faster than the crack growth rate near the threshold, thus hydrating the aluminum oxide and weakening the interface, causing interfacial failure [22]. This is similar to data reported for fracture tests in humidity-controlled environments using steel or aluminum adherends at a range of loading speeds [26]. Interfacial failure was only observed at low crack growth rates when moisture could diffuse ahead of the crack tip [26].…”
Section: Effect Of Environment On the P2-etched Aa6061-t6 Systemsupporting
confidence: 80%
“…Moreover, the development of epoxy adhesive has contributed to an increasingly important role of adhesive bonding in mechanical fastening due to its high static and fatigue strength, weight reduction, etc. However, the adhesive-bonded specimens are often easily damaged in certain environmental conditions such as high humidity as Kinloch et al (2007) and low temperature accordingly Miyoshi (1991). Therefore, the weld-bonded DP steel using epoxy adhesive which is a combination of RSW and adhesive bonding has been the subject of particular attention by Miyoshi (1995) and Darwish (2003).…”
Section: Introductionmentioning
confidence: 99%
“…[17] Water then decreases the mechanical properties of adhesive (tensile strength and Young's modulus) [4][5][6][7][8][9], may (depending on surface treatment) cause corrosion in the substrate at the interface [18][19][20], and hydration of strong metal oxides [21,22]. The consequences of the diffused water in the adhesive joint are reductions in the joint strength, both static [23][24][25][26][27][28] and fatigue [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…[19,35] Furthermore, water can swell the adhesive inducing the residual stress in the joint. [3] Finite element studies have revealed that the residual stresses due to swelling were sufficient to cause damage of the adhesive at the end of overlap.…”
Section: Introductionmentioning
confidence: 99%